Queen of the world - Hardman, Robert (Penguin Books, 2019)
On today's world stage, there is one leader who stands apart from the rest. Queen Elizabeth II has seen more of the planet and its people than any other head of state and has engaged with the world like no other monarch in modern history. The iconic monarch never ventured further than the Isle of Wight until the age of 20 but since then has now visited over 130 countries across the globe in the line of duty, acting as diplomat, hostess and dignitary as the world stage as changed beyond recognition. It is a story full of drama, intrigue, exotic and sometimes dangerous destinations, heroes, rogues, pomp and glamour, but at the heart of it all a woman who's won the hearts of the world.